Effect of Cooking Methods on Ascorbic Acid Destruction of Green Leafy Vegetables - Gebrehana Ashine Hailemariam; Tadele Andargie Wudineh (Journal of Food Quality)
Ascorbic acid is highly sensitive vitamin to various modes of cooking processes. Ethiopian green collards (Brassica carinata), locally called Ye’abesha Gomen, and cabbage (Brassica oleracea) are important green vegetables for ascorbic acid source in the country. The rate of ascorbic acid degradation in cabbage and Ethiopian green collard was studied employing two processing methods: open-pan and pressure cooking which are highly customized in household cooking. Samples were cooked at 5, 10, 15, 20, 25, 30, and 35 min under each processing method. Ascorbic acid concentration in each sample was determined by using a spectrophotometer at 520 nm wavelength using the standard plot of pure ascorbic acid solution. The initial concentration of ascorbic acid in fresh cabbage and Ethiopian green collard were found to be 33.76 ± 0.58 and 38.14 ± 0.19 mg/100 g, respectively. Well-cooked and edible Ethiopian green collard was obtained at 10 minutes of cooking time by pressure cooking with ascorbic acid retention of 31.8% from its initial contents. However, a cooking time of 25 min was required by the open-pan cooking method with 26.8% ascorbic acid retention. Edible cabbage was attained at 10 and 20 minutes of cooking time by pressure and open-pan cooking methods maintaining 36.9 and 30.9% of ascorbic acid, respectively. Thus, the pressure cooking method required short cooking time for having well-cooked and edible green leafy vegetable with better ascorbic acid retention. The outputs of this work would be helpful to design and control practical thermal processing situations and to minimize the loss of ascorbic acid in green leafy vegetables.